Efficient prediction of stochastic eye patterns via Lagrange interpolation. Issue 25 (1st December 2013) - Manfredi, P.; Stievano, I.S.; Canavero, F.G.
Abstract : The statistical assessment of system performance is addressed via the efficient estimation of eye diagram parameters under process variability. Statistical information pertaining to eye parameters is reconstructed by interpolation of a reduced set of simulations. The proposed strategy shows a remarkable efficiency improvement with respect to classical blind and brute‐force sampling‐based methods.